ISOLATION AND IDENTIFICATION OF SIMIARENOL FROM THE LEAVES OF FICUS AURANTIACEA GRIFF (MORACEAE) - L. B.S. Kardono; Lenny Sutedja; H. H.S. Fong; S-X Qiu (Research Center for Chemistry - LIPI, 2000)
Ficus aurantiace a Griff (Mor aceae) collected from BukitKaba forest park, Bengkulu, was studied for the isolation andidentification of its bioactive constituents. This plant is a climbingtree, having large colored fruits, orange to red marbled withwhite spots. The methanol-soluble extract of the leaves was eluted10 silica-gel column chromatography several times using mixturesof chloroform-methanol as the elution solvent, leading to theisolation of a known compound, simiarenol. The structure ofsimiarenol was judged by its data comparison to published values,and based all the evaluation results of its physical andspectroscopic data. such as UV, IR, MS, one- and two-dimensional NMR, HMQC and HMBC.